Microtus obscurus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
176. Altai Vole Microtus obscurus French: Campagnol obscur / German: Studostfeldmaus / Spanish: Topillo de Altai Other common names: Dark Vole Taxonomy. Hypudaeus obscurus Eversmann, 1841, probably near Chujskij trakt (a road), Altai Mtns., Russia. Microtus obscurus is in subgenus Microtus and arvalis species group. It is frequently regarded as a semi-species, subspecies, or group of populations of M. arvalis. There is no consensus on number of subspecies | of M. obscurus. Phylogeographic studies retrieved main evolutionary divergence on the Caucasus. Monotypic. Distribution. E Ukraine and Crimea, C, E & S European Russia, Georgia, E Turkey, Armenia, Azerbaijan, extreme NW Iran, N & E Kazakhstan, S Siberia (as far E as Tomsk and Kemerovo regions, and W Tuva), NW Mongolia, and NW China (Xinjiang). Descriptive notes. Head-body 101-136 mm,tail 32-51 mm; weight 23-48 g. In external and craniodental morphology, the Altai Vole is nearly identical to the Common Vole (M. arvalis). Tail is 28-3-40-6% of head—body length. Females have four pairs of nipples. Most individuals are dark brown on back, rarely yellowish brown or brownish buff, but flanks are more buff. Belly is gray and washed yellow. Skull is widely arched, with width across zygomatic arches accounting for ¢.56% of skull length. Sagittal crest is evident but low, and interorbital region is constricted in adults. Teeth are like those in the Common Vole. Habitat. Short grass meadows and arable lands from lowlands to mountain pastures at elevations up to ¢.3000 m. In central Asia, Altai Voles occupy semi-deserts, steppe, and forest steppe. Food and Feeding. The Altai Vole mainly depends on green leaves and stalks (79-100% of diet). Dietary contents depend on a season. In June, diets contain dandelion (Taraxacum) and sagebrush (Artemisia austriaca), both Asteraceae; clover (Trifolium, Fabaceae); bluegrass (Poa pratensis, Poaceae); purple-flowered garlic (Allium rotundifolium, Amaryllidaceae); and tulip (7ulipa, Liliaceae). In August, the Altai Vole mainly ...